Alignment of the magnetic circuit of the BIPM watt balance. (12th October 2015) - Bielsa, F; Lu, Y F; Lavergne, T; Kiss, A; Fang, H; Stock, M
Abstract: The International Bureau of Weights and Measures (BIPM) is developing a watt balance for the forthcoming redefinition of the kilogram. An improved version of the apparatus, based on a new closed magnetic circuit is now being assembled. The new apparatus will significantly reduce the type B uncertainty due to misalignment of the magnetic circuit as this work demonstrates. We present two techniques recently developed to accurately align the magnetic field of the circuit perpendicular to the direction defined by the local acceleration of gravity. Uncertainty below 30 μrad was achieved for both techniques which fulfils the requirements for the BIPM watt balance to enable a Planck constant determination at the 1 × 10 −8 level.